Subchronic toxic effects of bisphenol A on the gut-liver-hormone axis in rats via intestinal flora and metabolism - Wang, Jiaqi; Su, Ce; Qian, Mingqin; Wang, Xin; Chen, Changlan; Liu, Yangcheng; Liu, Wei; Xiang, Zheng; Xu, Baoli (Frontiers in Endocrinology, 2024)
Background Bisphenol A (BPA), a characteristic endocrine disruptor, is a substance that seriously interferes with the human endocrine system and causes reproductive disorders and developmental abnormalities. However, its toxic effects on the gut-liver-hormone axis are still unclear. Method Male and female rats were exposed to BPA (300 mg/kg) by oral gavage for 60 consecutive days. H&E staining was used for histopathological evaluation, and the serum biochemical indexes were determined using an automatic analyzer. The 16S rRNA gene sequencing was used to detect the intestinal microbial diversity, and the GC-MS was used to analyze the contents of short-chain fatty acids (SCFAs) in colon contents. UPLC-QTOF MS was used to analyze the related metabolites. The ELISA method was used to assess the levels of serum inflammatory factors. Results Histopathological analysis indicated that the liver, heart, and testis were affected by BPA. There was a significant effect on alanine aminotransferase (ALT), triglyceride (TG), total cholesterol (TC), and low-density lipoprotein (LDL) in the male-BPA group (P < 0.05), and globulin (GLB), indirect bilirubin (IBIL), alkaline phosphatase (ALP), ALT, TG, TC, high-density lipoprotein (HDL), and creatinine (Cr) in the female-BPA group (P < 0.05). Metagenomics (16S rRNA gene sequencing) analysis indicated that BPA reduced the diversity and changed the composition of gut microbiota in rats significantly. Compared with the control and blank groups, the contents of caproic acid, isobutyric acid, isovaleric acid, and propanoic acid in the colon contents decreased in the male-BPA group (P < 0.05), and caproic acid, isobutyric acid, isovaleric acid, and valeric acid in the colon contents decreased in the female-BPA group (P < 0.05). Metabolomic analysis of the serum indicated that BPA could regulate bile acid levels, especially ursodeoxycholic acid (UDCA) and its conjugated forms. The contents of amino acids, hormones, and lipids were also significantly affected after exposure to BPA. The increase in interleukin-6 (IL-6), interleukin-23 (IL-23), and transforming growth factor-β (TGF-β) in the serum of the male-BPA group suggests that BPA exposure affects the immune system. Conclusion BPA exposure will cause toxicity to rats via disrupting the gut-liver-hormone axis.